SEXUAL DIVERSITY, GENDER AND NEW FORMS OF FAMILY ORGANIZATION: ISSUES FOR EDUCATION AND COMMENSALITY - Roberta Ribeiro De Cicco; Eliane Portes Vargas (Universidade do Estado do Rio de Janeiro, 2016)
This article discusses the issue of sexual diversity, involving the transformation of gender identities in the practice of sexuality and the new organizational scenarios of contemporary family as related to inquiries and challenges in the teaching of science and the educational practices in their intersections with health, including eating habits. This issue has not been the interest and object of study often enough in these different contexts. In the present analysis, this issue is approached together with the knowledge and content that shape these practices with a view to socially legitimized role of school in educational processes and in the construction of scientific knowledge. The qualitative nature of reflections combine sociological and anthropological perspectives based on the collection of data on official documents, projects and/or initiatives that make sexual diversity a theme addressed in schools in order to strengthen the respect and legitimacy of conjugality between persons of the same sex. The debate points out the current social achievements as regards the right to form a family, added to the tensions that pervade the debate on sexual diversity involving public education policies. DOI: 10.12957/demetra.2016.22446